2017
DOI: 10.1177/2331216517743641
|View full text |Cite
|
Sign up to set email alerts
|

Age Dependence of Thresholds for Speech in Noise in Normal-Hearing Adolescents

Abstract: Previously found effects of age on thresholds for speech reception thresholds in noise in adolescents as measured by an online screening survey require further study in a well-controlled teenage sample. Speech reception thresholds (SRT) of 72 normal-hearing adolescent students were analyzed by means of the online speech-in-noise screening tool Earcheck (In Dutch: Oorcheck). Screening was performed at school and included pure-tone audiometry to ensure normal-hearing thresholds. The students’ ages ranged from 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In that respect, it is worrying to note that the background sounds in classrooms may reach 70-77 dB LAeq (Jamieson, Kranjc, Yu, & Hodgetts, 2004;Shield & Dockrell, 2003). When compared to adults, children show poorer word identification performance in noise at least until 10-11 years of age and more in some studies (Elliott, 1979;Elliott et al, 1987;Hall III et al, 2002;Jacobi, Sheikh Rashid, de Laat, & Dreschler, 2017;Johnson, 2000;Papso & Blood, 1989;Stuart, 2005Stuart, , 2008.…”
Section: A Perception Of Speech In Noise In Childhoodmentioning
confidence: 99%
“…In that respect, it is worrying to note that the background sounds in classrooms may reach 70-77 dB LAeq (Jamieson, Kranjc, Yu, & Hodgetts, 2004;Shield & Dockrell, 2003). When compared to adults, children show poorer word identification performance in noise at least until 10-11 years of age and more in some studies (Elliott, 1979;Elliott et al, 1987;Hall III et al, 2002;Jacobi, Sheikh Rashid, de Laat, & Dreschler, 2017;Johnson, 2000;Papso & Blood, 1989;Stuart, 2005Stuart, , 2008.…”
Section: A Perception Of Speech In Noise In Childhoodmentioning
confidence: 99%
“…A closer examination of the literature reveals that speech-in-noise recognition improves gradually over the first decade of life; adult-like performance is not usually observed until 9–10 years when stimuli are presented diotically (e.g., Eisenberg et al, 2000; Corbin et al, 2016; Buss et al, 2017; but see Jacobi et al, 2017). Corbin et al (2016) characterized the developmental trajectory for masked word recognition, including testing in the presence of speech-shaped noise.…”
Section: Speech-in-noise Recognitionmentioning
confidence: 99%
“…Cognitive processes are known to mature during adolescence (Luna, 2009; Peverill et al, 2016) and in support of the ELU-model’s predictions, studies have shown that younger teens require higher SNRs than older teens/adults when listening to speech in conditions that place demands on top-down processes (Stuart, 2008; Jacobi et al, 2017). Accordingly, age was shown in the current study to significantly covary with HINT performance as anticipated.…”
Section: Discussionmentioning
confidence: 88%